Leguminosae Juss. from Nascentes do Rio Parnaíba National Park, Brazilian Cerrado - Bastos, Maria Da Conceição De C.; Marinho, Lucas C.; Zappi, Daniela Cristina; Queiroz, Rubens Teixeira; Fernandes, Rozijane Santos (Phytotaxa, 2025)
A synopsis of the Leguminosae from the Park Nacional das Nascentes do Rio Parnaíba (PNNRP), located in the northern and northeastern regions of Brazil, is presented herein. A total of 68 species and 2 infraspecific taxa belonging to 29 genera and four subfamilies (i.e., Caesalpinioideae, Papilionoideae, Detarioideae, and Cercidoideae) were recorded. Of these, 14 species were considered new records for the northeastern or northern regions of Brazil, or for the states encompassing PNNRP. Genera with the highest number of species were Chamaecrista (15 spp.), Bauhinia (8 spp.), and Mimosa (6 spp.). Regarding plant physiognomies where the species were collected, Cerrado sensu stricto was predominant, followed by Cerradão and Veredas. Most of catalogued species had an unassessed conservation status, except for Bowdichia virgilioides, Chamaecrista coradinii, and Hymenaea parvifolia, which were classified as Near Threatened and Vulnerable, respectively. Treatment includes information on geographical distribution and taxonomic notes for species with an extended range.